Diversity Claims- Making in a Transnational Space of Mobilization: The Intersections of Gender and Ethnicity - Lise Rolandsen Agustín (The Royal Danish Library, 2010)
Diversity Claims-Making in a Transnational Space of Mobilization: The Intersections of Gender and Ethnicity Various organisations mobilise at the transnational, European level around gender and ethnicity issues, setting forward demands both by and on behalf of ethnic minority and migrant women. The organisations deal with diversity in terms of gender and ethnicity in different ways, but they all influence and are influenced by the EU framework. The intersectional nature of their diversity demands makes it necessary to combine particularistic claims regarding identity and European belonging with universal claims to human rights, citizenship and inclusion. The claimsmaking of the organisations is characterised by this complexity due to the transnational, multilevel nature of the demands, on one hand, and their intersectional features, on the other.